ANALYSIS OF THE USE OF VISUAL MEDIA IN LOW-GRADE ISLAMIC LEARNING AT SDN BANYUAJUH 2 KAMAL - Retno Maya Sealviana Firanti; Kusnaningsih; Rika Wulandari (maktab: Jurnal Pendidikan dan Teknologi, 2022)
In learning, learning media is very necessary, with the existence of learning media, it can increase students' interest in learning and understanding. One type of learning media that is most often used is visual learning media. Visual media is media used during learning that can be enjoyed by using the sense of sight. In learning in the subject of Islamic Religious Education visual media can be used to help students understand the material presented by the teacher. This research was conducted at SDN Banyuajuh 2 with the aim of analyzing the use of media by teachers in religious learning. The method used is descriptive method using interview techniques using a questionnaire. The interviews used were unstructured interviews which were carried out repeatedly in order to obtain objective, concrete, broad data. From this study it is known that for low grade students, only a few religious teachers provide learning media when delivering material. Teachers use more lecture methods and give assignments orally and in writing so that learning tends to be boring. After using visual media, students' interest in learning and learning motivation increased, causing students' understanding of the material to be better. Therefore, it can be concluded that the use of visual media can support the understanding of low grade students at SDN Banyuajuh 2 in the subject of Religion